Customer-oriented Design Support System : The Case of Eyeglasses Design Using Desktop Virtual Reality - Chuah, Kee Man; Roland, Alvinson; Teh, Chee Siong (2008)
The rapid-changing consumer market has encouraged many product designers to create products that are closely related to consumer’s psychological needs. Several methods have been introduced to aid such design goal but Kansei Engineering (KE) is the most notable tool that helps translates human feelings into design parameters. With the aid of advanced computer technologies, various computerised KE systems have been developed. However, the integration of desktop virtual reality in such system has yet to be fully explored. This paper presents the use of desktop virtual reality in the development of a customeroriented design support system. A case study on teen eyeglasses design is also presented to evaluate the proposed method. The findings revealed that desktop virtual reality provides a better user experience and help enhance consumers’ decision making.